A novel role for PsbO1 in photosynthetic electron transport as suggested by its light-triggered selective nitration in Arabidopsis thaliana. (2nd September 2018) - Takahashi, Misa; Morikawa, Hiromichi
ABSTRACT: Exposure of Arabidopsis leaves to nitrogen dioxide (NO2 ) results in the selective nitration of specific proteins, such as PsbO1. The 9th tyrosine residue ( 9 Tyr) of PsbO1 has been identified as the nitration site. This nitration is triggered by light and inhibited by photosynthetic electron transport inhibitors. During protein nitration, tyrosyl and NO2 radicals are formed concurrently and combine rapidly to form 3-nitrotyrosine. A selective oxidation mechanism for 9 Tyr of PsbO1 is required. We postulated that, similar to 161 Tyr of D1, 9 Tyr of PsbO1 is selectively photo-oxidized by photosynthetic electron transport in response to illumination to a tyrosyl radical. In corroboration, after reappraising our oxygen evolution analysis, the nitration of PsbO1 proved responsible for decreased oxygen evolution from the thylakoid membranes. NO2 is reportedly taken into cells as nitrous acid, which dissociates to form NO2 − . NO2 − may be oxidized into NO2 by the oxygen-evolving complex. Light may synchronize this reaction with tyrosyl radical formation. These findings suggest a novel role for PsbO1 in photosynthetic electron transport.